2016
DOI: 10.1002/ccd.26829
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of rotational atherectomy for the percutaneous treatment of chronic total occlusions

Abstract: The use of RA in CTO PCI was safe, despite a worse patient risk profile and higher procedural complexity, as compared with conventional techniques. Although procedural success was lower in the RA group, there were no differences in long-term clinical outcomes between groups. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
3
34
2
Order By: Relevance
“…In the present study, the technical and procedural success rates were >95% in both groups, which was in accordance with the rates reported in previous studies of RA in CTO-PCI. 11,22 In this work, we found that the number of RAs was much lower with retrograde PCI than with the anterograde approach, which was not beyond our expectation. The retrograde approach itself is also considered to be an effective alternative method for cases of “balloon uncrossable” CTO lesions.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In the present study, the technical and procedural success rates were >95% in both groups, which was in accordance with the rates reported in previous studies of RA in CTO-PCI. 11,22 In this work, we found that the number of RAs was much lower with retrograde PCI than with the anterograde approach, which was not beyond our expectation. The retrograde approach itself is also considered to be an effective alternative method for cases of “balloon uncrossable” CTO lesions.…”
Section: Discussionmentioning
confidence: 44%
“…The retrograde approach itself is also considered to be an effective alternative method for cases of "balloon uncrossable" CTO lesions. [20][21][22][23] For example, in the retrograde approach, the reverse CART technique can be applied to avoid the hard plaques of the CTO segment through subintimal tracking. Moreover, after achieving complete wire externalization with a retrograde guidewire crossing through the CTO segment, strong backup support is provided by the bilateral guide catheter anchor for equipment delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, slow‐flow/no‐reflow was noted in 17% of cases. Furthermore, their RA procedural success rate was significantly lower compared with the conventional PCI group (77% vs 88%, P = 0.04), while the long‐term MACE rate was similar between the RA and conventional group (15% vs 13%, P = 0.70) . Our results showed high success rate (96.2%) with low peri‐procedural complications (1 case), suggesting that RA might be a safe and effective technique for resistant CTO lesions.…”
Section: Discussionmentioning
confidence: 57%
“…In extreme cases, such as in balloon failure‐to‐cross, antegrade RA might be decisive. Few studies have specifically analyzed the outcomes of this technique in CTO patients , while most of available data on RA concern its use in non‐occlusive coronary artery disease .…”
Section: Discussionmentioning
confidence: 99%